Dileanation And A Role Of Mainstream To Dalit Feminism - et. al., Swapna Emmadi , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Dalit women have long occupied marginal positions and been excluded from two major Indian social movements: The Feminist Movement and the Dalit Movement. The researcher examines how Dalit women have made creative use of their marginality—their ‘outsider-within' status—and have represented their lived experiences. The study scrutinizes select life narratives of Dalit women writers: Bama's Sangati: Events (2005), Urmila Pawar’s The Weave of My Life (2015), and Baby Kamble’s The Prisons We Broke (2008) to discuss and explore the sociological significance of three characteristic themes in these narratives: (1) the interlocking nature of Dalitwomen’s oppression, (2) endurance and resilience, (3) their role in the transformation of the Dalit community. Thus, the perspectives of Dalit women writers create new knowledge about their lives, families, and communities. Their perspectives may well provide a preparatory point for the development of the Dalit Feminist Standpoint.